2020
DOI: 10.1136/jnnp-2020-324026
|View full text |Cite
|
Sign up to set email alerts
|

Split hand and motor axonal hyperexcitability in spinal and bulbar muscular atrophy

Abstract: ObjectiveThe ‘split hand’ sign refers to preferential wasting of the thenar and first dorsal interosseous muscles with relatively sparing of the hypothenar muscles in amyotrophic lateral sclerosis (ALS) and both cortical and spinal/peripheral excitotoxic mechanisms have been proposed. We aimed to study split hand and axonal excitability in spinal and bulbar muscular atrophy (SBMA) in which cortical motor neurons are intact.MethodsIn 35 patients with genetically confirmed SBMA, 55 with ALS, 158 with other neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Briefly, the excitability properties of CIDP were characterized by greater threshold changes in threshold electrotonus, presumably due to decreased myelin resistance by demyelination ( Cappelen-Smith et al, 2001 ). Patients with SBMA showed longer SDTC, suggesting increased persistent nodal sodium currents, possibly due to collateral sprouting ( Shibuya et al, 2020 ), consistent with previous reports.…”
Section: Resultssupporting
confidence: 91%
“…Briefly, the excitability properties of CIDP were characterized by greater threshold changes in threshold electrotonus, presumably due to decreased myelin resistance by demyelination ( Cappelen-Smith et al, 2001 ). Patients with SBMA showed longer SDTC, suggesting increased persistent nodal sodium currents, possibly due to collateral sprouting ( Shibuya et al, 2020 ), consistent with previous reports.…”
Section: Resultssupporting
confidence: 91%
“…Although split-hand syndrome is primarily associated with ALS, split-hand has been observed in other conditions, such as spinal muscular atrophy (SMA), spinocerebellar ataxia type-3, Kennedy's disease (SBMA) or postpolio syndrome. [11][12][13][14] A recent study suggested that the split-hand syndrome may be a feature of SBMA, although this finding was discordant when compared with a previous study from this group. 4 14 'Reverse split-hand syndrome', which refers to the predominant wasting of ADM and the relative sparing of APB, may suggest the diagnosis of Hirayama disease (HD) in the appropriate clinical context (box 1).…”
Section: Other Split Phenotypes In the Upper Limbsmentioning
confidence: 61%
“…Low temperatures slow the kinetics of the Na/K‐pump due to a reduction in its ATPase activity, leading to slow conduction velocity and muscle weakness 11,37,38 . Electrophysiological studies have suggested that upregulation of persistent nodal sodium conductance causes changes in axonal excitability, leading to motor neuron death 39 . Similarly, the depolarization of muscle fibers depends on the influx of Na+ ions; therefore, lower temperatures prolong the depolarization of each muscle fiber.…”
Section: Discussionmentioning
confidence: 99%
“…11,37,38 Electrophysiological studies have suggested that upregulation of persistent nodal sodium conductance causes changes in axonal excitability, leading to motor neuron death. 39 Similarly, the depolarization of muscle fibers depends on the influx of Na+ ions; therefore, lower temperatures prolong the depolarization of each muscle fiber. In a biological study, immunofluorescence revealed downregulation of CLCN1 protein in the muscles in a knock-in mouse model of SBMA, leading to abnormal sodium currents.…”
Section: Discussionmentioning
confidence: 99%